2018
DOI: 10.1128/aem.01201-18
|View full text |Cite
|
Sign up to set email alerts
|

Widely Used Benzalkonium Chloride Disinfectants Can Promote Antibiotic Resistance

Abstract: While misuse of antibiotics has clearly contributed to the emergence and proliferation of resistant bacterial pathogens with major health consequences, it remains less clear if the widespread use of disinfectants, a different class of biocides than antibiotics such as benzalkonium chlorides (BAC), has contributed to this problem. Here, we provide evidence that exposure to BAC co-selects for antibiotic-resistant bacteria, and describe the underlying genetic mechanisms. BAC-fed bioreactors inoculated with river … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
150
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(168 citation statements)
references
References 68 publications
3
150
1
4
Order By: Relevance
“…They concluded that the persistent populations on the cannery lines were not inherently more tolerant to the disinfectant but that other factors (ie, surface attachment, biofilm formation, and growth rate) were likely responsible for their ability to persist in the disinfectant-treated environment. Kim et al (2018) 17 examined the impact of continuous exposure to BK on bacterial populations isolated from contaminated river sludge. The sediment samples were maintained for extended periods (3 years) in bioreactors containing nutrient medium and increasing concentrations of BK or nutrient medium alone.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the persistent populations on the cannery lines were not inherently more tolerant to the disinfectant but that other factors (ie, surface attachment, biofilm formation, and growth rate) were likely responsible for their ability to persist in the disinfectant-treated environment. Kim et al (2018) 17 examined the impact of continuous exposure to BK on bacterial populations isolated from contaminated river sludge. The sediment samples were maintained for extended periods (3 years) in bioreactors containing nutrient medium and increasing concentrations of BK or nutrient medium alone.…”
Section: Discussionmentioning
confidence: 99%
“…This paper as well as a few other publications highlight the detrimental effects of using benzalkonium chloride in laundry detergents and bath oils. [3][4][5] This would be an opportune moment for the Australasian College of Dermatologists and other similar scientific bodies to bring this to the notice of the public, detergent industry stake holders and relevant government agencies, with a view to stopping the practice of adding unnecessary antifungal and antibacterial additives to laundry detergents. Such additives do not have any proven benefit in preventing infections.…”
Section: Correspondence Lettermentioning
confidence: 99%
“…4 Only once the public has mastered these basic sun protection modalities can the medical community introduce more novel and experimental modalities of sun protection. 5 Vangelis George Kanellis 1 | Alice Louise Kanellis 2 | Lena Von Schuckmann 3 |…”
Section: Correspondence Lettermentioning
confidence: 99%
“…We next sought to demonstrate that ROSALIND could be used to sense two PPCP compounds: (1) salicylate, a widely used compound in personal care products [48] that has been shown to bind to the Staphylococcus aureus MarR-family aTF SAR2349 [53], and (2) benzalkonium chloride, a widely used disinfectant that can promote antimicrobial resistance [54], and has been shown to bind to the Staphylococcus aureus TetR-family aTF QacR [55]. When these purified aTFs and the corresponding operator-containing DNA constructs were included in ROSALIND reactions, we were able detect these two PPCP compounds at a high micromolar to low millimolar range ( Fig.…”
Section: Rosalind Can Be Modularly Reconfigured To Sense Antibioticsmentioning
confidence: 99%